Estudio de los programas de tratamiento en adicción al consumo de alcahol en los pacientes del centro de recuperación Divino Cristo de la ciudad de Machala en el año 2014. - Barriga Macía, Luis Alberto (2014)
One of the alternatives offered positive process of rehabilitation of the alcohol dependent persons results are treatment programs that are used in different psychotherapeutic centers in the country, but therefore it becomes relevant research rehabilitation processes aiming to determine the level of impact of the rehabilitation process, aiming at determining the level of impact of treatment programs for alcohol addiction.